Dialect loss in the Russian North: Modeling change across variables. (October 2019) - Daniel, Michael; von Waldenfels, Ruprecht; Ter-Avanesova, Aleksandra; Kazakova, Polina; Schurov, Ilya; Gerasimenko, Ekaterina; Ignatenko, Daria; Makhlina, Ekaterina; Tsfasman, Maria; Verhees, Samira; Vinyar, Aleksei; Zhigulaskaja, Vasilisa; et al.
Abstract: We analyze the dynamics of dialect loss in a cluster of villages in rural northern Russia based on a corpus of transcribed interviews, the Ustja River Basin Corpus. Eleven phonological and morphological variables are analyzed across 33 speakers born between 1922 and 1996 in a series of logistic regression models. We propose three characteristics for a comparison of the rate of loss of different variables: initial level, steepness, and turning point. We show that the dynamics of loss differs significantly across variables and discuss possible reasons for such differences, including perceptual salience, initial variation in the dialect, and convergence with regionally or socially defined varieties of Russian. In conclusion, we discuss the pros and cons of logistic regression as an approach to quantitative modeling of dialect loss. Our paper contributes to the study and documentation of Russian dialects, most of which are on the verge of extinction.